Procedimento comportamental para redução de estereotipias em crianças com TEA: uma revisão sistemática - Silva, Helena de Paula (Universidade Federal de São Carlos, 2023)
Stereotyped self-injury can be defined as intense repetitive behaviors that occur with high frequency and little variation; when these movements are performed by the child causing physical damage they are called self-injury or self-injurious behaviors, which can compromise the daily functioning of people with Autism Spectrum Disorder (ASD). Thus it should be noted that teaching procedures are working strategies that aim to institute new alternative behaviors by reinforcing the appropriate operant behavior class, in order to reduce disruptive behaviors. The main objective of this research was to identify which teaching procedures have been used in children with ASD who present disruptive behaviors. And as a specific goal, to understand if the teaching procedures of the included researches helped or not, in the reduction of stereotypical behaviors. To this end, a systematic literature review will be conducted in the Journal of Applied Behavior Analysis (JABA) platform in the last five years, between the years 2017 and 2022, with qualitative analysis of the data. As a result, 8 articles were found and analyzed in full. Such studies revealed that in general: (1) perceive/identify the effect of procedures in reducing stereotypy; (2) There is a higher prevalence of boys than girls; (3) greater predominance of research involving only vocal stereotypies; (4) the most used teaching procedure was the Response Interruption and Redirection Procedure (RIRD). Thus it is highlighted that teaching procedures are effective, socially relevant for decreasing stereotypy and fundamental for the improvement of strategies and application with individuals with ASD, to understand and bring benefits to individuals.
Behavioral procedure for reducing stereotypies in children with ASD: A systematic review
Keywords: Educação Especial; Transtorno do Espectro do Autismo; Estereotipia; Special Education; Autism Spectrul Disorder; Stereotyping; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO